In Sonbhadra District in Uttar Pradesh... Technological intervention to revolutionize Tribals’ livelihood - Singh, B.; Singh, Neeraj; Roy, Shubhadeep; Rai, A. B.; Prasad, R. N.; Chaurasia, S.N. S.; Pandey, Sudhakar; Chaturvedi, A. K.; Pandey, Rakesh; Chaudhary, R. P. (Indian Horticulture, 2019)
Rural tribal in Sonbhadra district of Uttar Pradesh have great potential of farming but due to lack of technical know-how and living in isolation causes low productivity of crops. Here credit carries a high-interest price tag, whereas the tribal people produce are brought at a fraction of the market rate. This transformation has meant a decline in both the tribes security and their standard of living. Considering the facts, an approach was made by IIVR, Varanasi, in these tribal regions through desired training, farmers’ meetings and frontline demonstrations of vegetables & field crops production technologies along with kitchen garden and backyard poultry showed a positive impact in the tribals’ field compared to the existing cultivars, in terms of quality, productivity and market value. The efforts have also resulted in sustainable livelihood and nutritional security of the tribal farm families and opened a better scope of employment generation in terms of farming, agri-labour, marketing and processing.